Performance With Good Corporate Governance As Moderation - Cicilia Cicilia; Lindrawati Lindrawati (JAFFA, 2021)
The purpose of this study is to analyze the effect of sustainability reporting on financial performance with good corporate governance as moderation. The research design used is quantitative with a hypothesis. The type of data used is quantitative and qualitative data, that is sustainability reports, annual reports, and CGPI reports. All data is secondary data. The research objects are all companies that participated in the research and CGPI ranking in 2013-2017. Data analysis techniques used in this study are simple, multiple, and moderated linear regression. The results showed sustainability reporting had positive effect on financial performance. Sustainability reporting economic and social dimensions do not affect, while environment dimension has positive effect on financial performance. Good corporate governance can’t moderate the effect of sustainability reporting both overall and per dimension on financial performance.